Peculiarities of assessing the economic efficiency of major well repairs of unprofitable gas and gas condensate fields of the Stavropol krai - Z. S. Dotdueva; G. V. Chepurko; A. M. Kravtsov (Вестник Северо-Кавказского федерального университета, 2023)
Gas industry plays a significant role in the economy of the Stavropol Krai, providing other industries with necessary natural resources and employment for a significant part of the population. However, in modern conditions, it has a number of problems that hinder its dynamic development. One of them is the final stage of field development, characterized by a decrease in hydrocarbon production, a worn-out state of wells and the in-field transport system. One of the ways to solve these problems is the timely overhaul of wells, which will allow maintaining the level of hydrocarbon production at a given level and save jobs. The implementation of these measures requires significant investments, therefore, when planning the volume and timing of their implementation, it is necessary to give a preliminary technical and economic assessment in order to determine their effectiveness. This study analyzes the major repairs of wells carried out at the fields of the Stavropol Krai over the past ten years, identifies the main causes of well stoppage, determines the consequences for the development of the field from the untimely disposal of wells. The authors analyzed the existing methodology for assessing the economic efficiency of well capital repairs, and proposed additions that allow taking into account not only the stage of field development, but also social consequences due to the refusal to carry out capital repairs of the well.